Предмет: Алгебра,
автор: Аноним
-0,6x(x+0,3)-(0,4x+1)
(6a-7)(7+6a)+(7-8a)-8a
упростить
Ответы
Автор ответа:
0
-0,6x(x+0,3)-(0,4x+1)
(6a-7)(7+6a)+(7-8a)-8a= -0,6х²-0,18-0,4х+42а+36а²-49-42а+7-8а-8а= 35,4х²-42,18-0,4х-16а
(6a-7)(7+6a)+(7-8a)-8a= -0,6х²-0,18-0,4х+42а+36а²-49-42а+7-8а-8а= 35,4х²-42,18-0,4х-16а
Похожие вопросы
Предмет: Русский язык,
автор: malikovich
Предмет: Математика,
автор: jojo5655
Предмет: Математика,
автор: charly07
Предмет: Обществознание,
автор: adaspots
Предмет: Математика,
автор: NinaSFS